The Effect of Theme-Based Storytelling and Flash Card on Nutritional Knowledge in Early Childhood Education - Setiana, Yuni Nuraeni; Handayani, Oktia Woro Kasmini; Suminar, Tri (Journal of Primary Education)
The purpose of this study was to determine the effect of theme-based storytelling and flashcards nutrition knowledge in Early Childhood Education (ECE). This research was a quantitative research with quasi-experimental equivalent pre-test – post-test control group design. The population was Kindergarten Merpati group in Margorejo, Pati which have 251 children. The sampling technique was purposive sampling. The samples were Pertiwi Kindergarten Langenharjo (32 children), Pertiwi Kindergarten Dadirejo (32 children), Pertiwi Kindergarten Penambuhan (32 children). Data were obtained from non-test techniques consisting of interview, documentation, and observation. Observations were made to see the children' activities before and after intervention about nutritional knowledge through a questionnaire. The data were analyzed by paired sample t-test and one-way analysis of variance. Furthermore, post hoc tests were used to analyze the most optimal interventions. The results showed that the theme-based storytelling method improved children’ nutritional knowledge by 24.45%, the theme-based flashcard media improved children’ nutritional knowledge by 31.84%, the theme-based flashcard was the most influential intervention on children’ nutritional knowledge improvement.